Screening of Crude Extract of Flavonoids of Moringa oleifera against Bacteria and Fungal Pathogen - Talreja*, Tamanna (Journal of Phytology, 2010)
Crude extracts were prepared from the flowers and callus of Moringa oleifera using ethanol extract and screened for their antimicrobial activity against some bacteria andfungal pathogen by paper disc method. The tested gram positive bacterial strains were Bacillus subtilis and Staphylococcus aureus, gram negative bacterial strains were Escherichia coli, Klebsiella pneumoniae and fungal pathogen Candida albicans. Although flavonoids are present in all parts of Moringa oleifera, maximum amount was observed in flowers. Hence soxhlet extract of 5 grams of powdered flowers and unorganized tissues of M. oleifera were screened for their antimicrobial activity. Among the flowers and unorganized tissue tested, the ethanol extract of callus exhibited higher antimicrobial activity when compared to the floral extract. Key words: Antimicrobial, Antifungal, Moringa oleifera, Soxhlet extract, Ethanol extract <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Tamanna Talreja. Screening of Crude Extract of Flavonoids of Moringa oleifera against Bacteria and Fungal Pathogen. J Phytol 2/11 (2010) 31-35